A DFT study on interaction between Au, Re and Au-Re surfaces with species involved in WGS reaction - Uzun, Ali. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2012., 2012)
In this study, the steps of WGS reaction was investigated through studying the adsorption/co-adsorption of its reactants, products and possible intermediate species on Au(111), Re(001) and Au-Re(001) surfaces at atomic scale via utilizing DFT modules of CASTEP. Firstly, the adsorption energies of CO, OH, CO2, H2O, HOCO molecules and H atoms on Au(111) and Re(001) surfaces, LDOS profiles of these adsorbates for their free and in adsorbed state, and the surface metal atoms on the adsorption sites of Au(111) and Re(001) surfaces for their bare and adsorbed state were analyzed. Additionally, CO-OH co-adsorption on Au(111) and Re(001) surfaces were carried out in order to analyze the reaction steps of WGS reaction on Au(111) and Re(001) surfaces. In the second part of the study, Au-Re surface alloys were generated by the addition of Au atoms on Re(001) surface as point defects. The adsorptions/co-adsorptions of CO and OH molecules on Au- Re(001) surface alloys having different Au concentration on Re(001) were carried out in order to understand the reason of high activity and selectivity of Au-Re/Ceria catalysts. The results revealed that monometallic Au and Au-Re surface alloy are active catalysts, whereas Re is not an active catalyst for WGS reaction. It was found that OH has stronger interaction with Au surface than that of CO in terms of its high binding energy, and it is inferred that the active sites on Au surface, which dominantly participate in WGS reaction steps, can be poisoned by OH molecules due to site competition. The results also showed that the binding energies of OH on Re are higher than that of OH on Au, and it is concluded that OH molecules can move from Au sites to Re sites, and the active sites on Au surface can be poisoned by OH molecules to a lesser degree. The co-adsorption of CO and OH molecules on Au(111), Re(001) and Au-Re surfaces revealed that WGS reaction takes place on Au sites of monometallic and Au-Re surface alloy, and the surface reaction between CO and OH molecules on Au is consistent with the carboxyl mechanism.
Keywords: Quantum theory.; Water-gas.; Catalysts.; Gold alloys.; Rhenium.